2017
DOI: 10.1039/c7fo00819h
|View full text |Cite
|
Sign up to set email alerts
|

Mice gut microbiota programming by using the infant food profile. The effect on growth, gut microbiota and the immune system

Abstract: During the complementary feeding (CF) period, nutritional imbalances can have negative consequences not only on a child's health in the short term but also later in adulthood, as a phenomenon known as "nutritional programming" takes place. The aim of this study was to evaluate the possible changes in body growth, gut microbiota (GM) and the immune system in mice fed with two different commercial sterilized baby foods in jars (BFJs) for CF. Mice fed with different BFJs (A and B groups) showed an accelerated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
4
0
3
Order By: Relevance
“…Sequencing of the 16S rRNA V3 gene resulted in a total of 281,1112 reads with a minimum and maximum number of reads per sample of 9,411 and 123,598; with 2,250 assigned OTUs. Alpha diversity measured by Shannon index (Figure 5A) significantly decreased (P < 0.0001) in all dietary intervention groups over the four weeks prior to DSS treatment, likely reflecting compositional changes when transitioning from mother's milk to standard mouse chow (34)(35)(36). However, significant differences in alpha diversity were not observed between vitamin B12 deficient, sufficient or supplemented groups of mice after 28 days on respective diets.…”
Section: Altered Vitamin B12 In the Diet Does Not Affect Gut Microbiamentioning
confidence: 96%
“…Sequencing of the 16S rRNA V3 gene resulted in a total of 281,1112 reads with a minimum and maximum number of reads per sample of 9,411 and 123,598; with 2,250 assigned OTUs. Alpha diversity measured by Shannon index (Figure 5A) significantly decreased (P < 0.0001) in all dietary intervention groups over the four weeks prior to DSS treatment, likely reflecting compositional changes when transitioning from mother's milk to standard mouse chow (34)(35)(36). However, significant differences in alpha diversity were not observed between vitamin B12 deficient, sufficient or supplemented groups of mice after 28 days on respective diets.…”
Section: Altered Vitamin B12 In the Diet Does Not Affect Gut Microbiamentioning
confidence: 96%
“…Recent studies have indicated that it is necessary to continue investigating the interaction between GM and the epithelial cells of the GI tract because GM seems to act as an epigenetic regulator of several diseases (Kumar et al, 2014). Thus, dysbiosis or imbalances in the GM can induce intestinal inflammation that is associated with the pathogenesis of several diseases such as obesity, Crohn's disease, irritable bowel syndrome, Obsessive-Compulsive Disorder, Depression, Anxiety, type 2 diabetes mellitus and neurodegenerative diseases including Alzheimer's and ASD (Durbán et al, 2012;Mangiola et al, 2016;Schäffler et al, 2016;Ding et al, 2017;Pradhan et al, 2017;Sanchez-Samper et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, GI symptoms appear to be due, in part, to dysbiotic GM. In this sense, there is enough scientific evidence regarding the relationship between a dysbiotic GM and the development of diverse chronic diseases such as asthma, intestinal inflammation associated with the pathogenesis of obesity, type 2 diabetes mellitus [12], and other neurodevelopmental disorders [13].…”
Section: Introductionmentioning
confidence: 99%